2008
DOI: 10.1128/jvi.01052-08
|View full text |Cite
|
Sign up to set email alerts
|

The M, E, and N Structural Proteins of the Severe Acute Respiratory Syndrome Coronavirus Are Required for Efficient Assembly, Trafficking, and Release of Virus-Like Particles

Abstract: . This suggests that the mechanism of SARS-CoV assembly differs from that of other studied coronaviruses, which only require M and E proteins for VLP formation. When coexpressed, the native envelope trimeric S glycoprotein is incorporated onto VLPs. Interestingly, when a fluorescent protein tag is added to the C-terminal end of N or S protein, but not M protein, the chimeric viral proteins can be assembled within VLPs and allow visualization of VLP production and trafficking in living cells by state-of-the-art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
507
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(544 citation statements)
references
References 71 publications
13
507
0
12
Order By: Relevance
“…A wide range of trackable VLPs has been generated by labeling one or more viral components with a fluorescent protein (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Many VLPs have been labeled after particle production/ purification, usually by chemical coupling to (in)organic Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of trackable VLPs has been generated by labeling one or more viral components with a fluorescent protein (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Many VLPs have been labeled after particle production/ purification, usually by chemical coupling to (in)organic Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…The route of vaccine administration directly influences both the quality and quantity of vaccine-induced immunity [105108]. Traditional parenteral administration routes, such as i.m., intradermal, and s.c., have been shown to induce favorable immune responses and/or protection against SARS-CoV and MERS-CoV infections [57, 109111]. It is demonstrated that i.m.-vaccination with RBD protein of SARS-CoV elicits long-term immune responses with neutralizing activity, protecting immunized mice from SARS-CoV challenge [50].…”
Section: Potential Strategies For Developing Mers Vaccinesmentioning
confidence: 99%
“…The avian infectious bronchitis virus (IBV) M protein contains Golgi-targeting information in its first transmembrane domain [14], whereas the transmembrane domains and the cytoplasmic tail domain of the mouse hepatitis virus (MHV) M protein play important roles in Golgi targeting [15,16]. The M protein interacts with the E, S, and N proteins and plays an essential role in virus assembly [17,18,19]. M is a necessary component of virus-like particles (VLP) during viral assembly [18,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The M protein interacts with the E, S, and N proteins and plays an essential role in virus assembly [17,18,19]. M is a necessary component of virus-like particles (VLP) during viral assembly [18,20,21,22]. The M proteins interact other M proteins to form homo-oligomers [23].…”
Section: Introductionmentioning
confidence: 99%